Common Clinical signs and symptoms observed in Patients diagnosed with Thyrotoxicosis in Gujranwala, Pakistan - Muhammad Adnan Iqbal, Sadia Rashid, Saveela Sadaqat, Nadia Junaid, Muhammad Rizwan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the common clinical sign and symptoms in Patients of Thyrotoxicosis in Gujranwala, Pakistan. This study was conducted at the Civil Hospital and Salamat Hospital & Healthcare Center, Gujranwala from July 2019 to February 2020. Methods: This was a prospective study consisted of 120, male and female patients of different age groups, diagnosed with thyroid gland disorder. The Clinical features and history related to thyroid disorders was taken. Complete thyroid profile was checked in initial screening of Thyrotoxicosis.The bloodscreening for various thyroid hormonal levels,Thyroid imaging for the patients with neck swelling and clinically various thyroid function tests were done by using Radiation Imaging (Radiotracers) techniques. Aninformed consent of all patients was taken before tests and study. The data was recorded on designed Performa. Results: In this study the prevalence of Thyrotoxicosis patients was higher in females (78) than male (42) and majority of patients belonged to 31-50 years of age range. Various typical clinical sign and symptoms of Thyrotoxicosis like Goiter, sweating, heat intolerance, Hoarseness, Tremors, Diarrhoea, anxiety, hair loss, Menstrual irregularities in females, Exophthlmus, increased appetite and poly urea were observed in patients diagnosed with Thyrotoxicosis.While in blood screening, marked mean ±SD of BMI, free T3ng/dL, T4(ng/dL) and TSH(mlU/L) were found in male & female patients (table 2). Conclusion and practical implication: Thyroid casesare found high in our population. This high prevalence rate is affecting the health and quality of life of affected persons. So it is deeply felt that awareness to use dietary iodineand other remedies isa need of hour for our communities to decrease high prevalence of the thyroid dysfunctions and improve health and quality of life of the community. Keywords: Thyrotoxicosis, Radiotracers, Radiation Imaging Technique, Signs and Symptoms, TSH, T3 and T4, Prevalence.